2016
DOI: 10.1038/srep21663
|View full text |Cite
|
Sign up to set email alerts
|

Caveolae Restrict Tiger Frog Virus Release in HepG2 cells and Caveolae-Associated Proteins Incorporated into Virus Particles

Abstract: Caveolae are flask-shaped invaginations of the plasma membrane. Caveolae play important roles in the process of viruses entry into host cells, but the roles of caveolae at the late stage of virus infection were not completely understood. Tiger frog virus (TFV) has been isolated from the diseased tadpoles of the frog, Rana tigrina rugulosa, and causes high mortality of tiger frog tadpoles cultured in Southern China. In the present study, the roles of caveolae at the late stage of TFV infection were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…CAV2 is a protein component of caveolae structures. A recent study demonstrated that the caveolae and, therefore, its components could act as restriction factor for Tiger Frog Virus (TFV) release in late steps of viral cycle [ 86 ] in another hepatocyte cell line, HepG2. As OROV entry is mediated by clathrin-endocytosis [ 16 ], we speculate that caveolae could be a restriction site for viral budding/release; therefore down-regulation of a structural component could favors viral release.…”
Section: Discussionmentioning
confidence: 99%
“…CAV2 is a protein component of caveolae structures. A recent study demonstrated that the caveolae and, therefore, its components could act as restriction factor for Tiger Frog Virus (TFV) release in late steps of viral cycle [ 86 ] in another hepatocyte cell line, HepG2. As OROV entry is mediated by clathrin-endocytosis [ 16 ], we speculate that caveolae could be a restriction site for viral budding/release; therefore down-regulation of a structural component could favors viral release.…”
Section: Discussionmentioning
confidence: 99%
“…Although the combined data suggest a function of caveolae in viral biogenesis, an association with caveolin-1 alone does not directly demonstrate the involvement of caveolae in virus morphogenesis. In addition, siRNA-mediated knockdown of caveolin-1 was shown to have no effect on RSV morphogenesis and infection in cultured cells ( Kipper et al, 2015 ), and there is some evidence that caveolin-1 might have an anti-viral role during virus infection ( Gabor et al, 2013 ; Bohm et al, 2014 ; He et al, 2016 ). Thus, the role of caveolin-1 and caveolae in virus-infected cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…For this work, we set out to test whether PTRT might have some endocrine/paracrine influence beyond its effect as endogenous factor. Some studies have already reported the presence of extracellular PTRF in viral capsids [9] and in bladder cancer exosomas [24].Yet, this is the first report showing that PTRF circulates in the blood of individuals free of cancer or any viral disease. Moreover, we also proved that PTRF associated with exosomes.…”
Section: Discussionmentioning
confidence: 72%